“The whole is greater than the sum of its parts” – Exploring teachers’ technology readiness profiles and its relation to their emotional state during COVID-19 emergency remote teaching - Pozas, Marcela; Letzel-Alt, Verena; Schneider, Christoph (Frontiers in Education, 2022)
With the rapid spread of the Coronavirus (COVID-19), schools around the world came to a shutdown. This resulted in an abrupt transition from face-to-face instruction to emergency remote teaching (ERT), resulting in numerous challenges that have greatly affected teachers. Even though research has identified key factors for teachers to effectively implement ERT in the context of the COVID-19 school shutdown, there is still little research on the factors (and their interrelations) that account for the differences between teachers’ experiences. This study aimed to investigate teacher profiles based on technology readiness domains. In addition, this study seeks to explore whether teachers’ emotional state during ERT varies between the teacher technology readiness profiles. A total of 124 teachers participated voluntarily in an online survey stemming from the research project ‘Students-Parents-Teachers in Homeschooling’ in Germany. Results from a two-step cluster analysis revealed three distinct teacher technology readiness profiles. Moreover, the findings also revealed gender differences between the three technology readiness profiles. Lastly, an analysis of variance indicated that teachers’ positive emotional state during ERT varied significantly across the clusters. Implications of the results for teacher education and teacher professional development, as well as further lines of research are discussed.